Factors Leading To Success Of Tourism Business In Bangkok Thailand - Kerdpitak, Chayanan (Journal of Applied Business Research, 2017)
The research on Factors Leading to the Success of a Tourism Business aims to 1) study the current condition of the tourism business 2) study the guideline for tourism business development 3) study marketing innovation and tour program arrangement and the competition strategies of the tourism business 4) study the business success of the tourism business management 5) study the influencing factors to business success of tourism business. Quantitative and qualitative researches have been applied as research methodology. The population includes tourism companies in Bangkok. The unit of analysis is a tourism organization. The simple random sampling is used to select the sample for the quantitative research. The sample used for data collection includes 339 tourism business operators and managers, and the instrument used is a questionnaire. The purposive sampling method selection is used to collect the sample for the qualitative research. The data have been collected from the tourism business operators or managers by means of in-depth interview. The data have been analyzed by using the descriptive statistics, and the path analysis has been applied for equation analysis. According to the study result, the factors of the marketing innovation, the tour program arrangement and the competition strategies influence the business success of the tourism business management by having the influential level of 42.6 percent. There are 45 main factors that can be used for the success of the business. The current condition of the tourism business is highly competitive. Marketing innovations are always applied for the competition. In addition, the tour program arrangement is significant, and it must be adjusted for the high season. The guideline used for the tourism business development includes the differentiation of the tour program arrangement, the price and the service quality, such as accommodations, vehicles, food, safety and clients’ needs.